On the Quantity and Quality of Girls: New Evidence on Abortion, Fertility, and Parental Investments - S Anukriti; Sonia R. Bhalotra; Hiu Tam (Institute for the Study of Labor (IZA), 2016)
The introduction of prenatal sex-detection technologies in India has led to a phenomenal increase in abortion of female fetuses. We investigate their impact on son-biased fertility stopping behavior, parental investments in girls relative to boys, and the relative chances of girls surviving after birth. We find a moderation of son-biased fertility, erosion of gender gaps in breastfeeding and immunization, and complete convergence in the post-neonatal mortality rates of boys and girls. For every five aborted girls, we estimate that roughly one additional girl survives to age five. The results are not driven by endogenous compositional shifts, being robust to the inclusion of mother fixed effects. Our findings have implications not only for counts of missing girls but also for the later life outcomes of girls, conditioned by greater early life investments in them.
Keywords: I15; J13; J16; 330; abortion; child mortality; fertility; gender; health; India; missing girls; parental investments; prenatal sex detection; sex-selection; ultrasound